Ресурси особистості як чинник стресостійкості державних службовців - Дорош, І. М.; Dorosh, I. (Видавництво Львівської політехніки, 2020)
Здійснено теоретичний аналіз змісту ресурсної концепції стресу, визначено важливість прикладного застосування цього підходу в галузі вітчизняного публічного управління, який може стати підґрунтям для вирішення проблем підвищення рівня стресостійкості державних службовців. Для цього наведено модель професійного стресу, що запропонував Дж. Грінберг, яка дає можливість зрозуміти важливість особистісних характеристик працівника для конструктивного вирішення стресових ситуацій. Розкрито також зміст поняття “копінгу” як своєрідного типу подолання стресової ситуації, стратегії поведінки. Розглянуто базову класифікацію копінг-стратегій, яку запропонували Р. Лазарус та Фолкман, а також низку конкретних стратегій копінгу, що характеризують базові класифікаційні групи. В ході аналізування результатів власних емпіричних досліджень встановлено, що забезпечення високого рівня стресостійкості державних службовців – результат вдалого поєднання наявних особистих ресурсів фахівця на етапі його працевлаштування із постійним саморозвитком, навчанням, набуттям досвіду тощо.

The article provides a theoretical overview of the categories of the resource concept of stress and identifies their applied aspect in the field of domestic public administration. After all, the civil service is a special type of management activity, which is characterized by a high level of social responsibility, publicity and, as a rule, insufficient motivation. In addition, the civil service is classified as an activity with high human requirements. To do this, there is presented the model of occupational stress, proposed by J. Greenberg, which provides an opportunity to understand the importance of personal characteristics of the employee in the process of constructive resolution of stressful situations. After all, the ability to adapt to changes in the environment, the perception of threats can both strengthen and weaken internal organizational sources of stress and external, outside the organization. The presented model focuses on the negative consequences, namely the deterioration of employee health due to stress at work. It is also disclosed the concept of “coping” as a unique type of overcoming a stressful situation, the strategy of behavior. The basic classification of coping strategies proposed by Lazarus and Folkman is considered, as well as a number of specific coping strategies that characterize the basic classification groups. In addition, there are two approaches to the study of coping, namely: deductive and inductive. The deductive method is based on the study of existing literature and the results of coping research. The inductive method is to analyze people’s actions and opinions in certain situations without imposing specific coping strategies on the basis of a survey. A person’s resources are his knowledge, skills, abilities, emotional and social intelligence, which together form his stress resistance, the habit of choosing certain coping strategies to overcome stressful situations. This is the essence of the resource concept of stress. In the initial stages of stress, a person spends personal resources to eliminate stress factors. Its protective response is activated at the stage of scarcity of these resources and is due the need to restore them. In the case of exhaustion, when it is not possible to replenish lost resources, a person is exposed to psychological stress, which leaves its negative impact on the results of the work. Thus, we can conclude that stress is not a constant characteristic of the individual. It is dynamic: in case of deficiency of personal resources – the level of stress resistance decreases. In accordance with the accumulation and conservation of these resources – the level of stress resistance will increase. Therefore, ensuring a high level of stress resistance of civil servants is the result of a successful combination of available personal resources of a specialist at the stage of his employment with constant self-development, training, gaining experience, etc. Because an important factor in choosing the right coping strategy of the individual is its resourcefulness.
Personal resources as a factor of stress resistance of civil servants
Keywords: ресурси особистості; ресурсна концепція стресу; копінг; емоційний інтелект; державна служба; personality resources; resource concept of stress; coping; emotional intelligence; civil service; J24; 35; 658.3